Possibilities of reducing the volume of plastic packaging for consumer chemicals - Paták, Michal; Branská, Lenka; Pecinová, Zuzana (University of Pardubice, 2020)
One of the most significant environmental problems currently addressed is an effort to reduce the volume of plastic used for packaging. Theoretically, the volume of plastic packaging can be reduced in a number of ways, but not all of them are practically applicable. So far, it is not yet clear which savings options for primary plastic packaging are suitable for consumer chemicals (detergents, washing and sanitary products). This article offers one of the possible approaches for such savings. It presents the results of primary qualitative research whose main objective was to reveal innovations of primary plastic packaging for consumer chemicals that would be feasible by the manufacturer and, at the same, appreciated by customers. The research reported herein was carried out in two consecutive stages. The first one was realized in a company which can be considered a typical producer of consumer chemicala focused on the identification of possibilities to save plastic waste from primary packaging from the manufacturer's point of view. In this research, the method of semi-structured interview was used; the main respondent being the process engineer of the company. The second stage was carried out with final consumers with a focus on revealing the main environmental requirements of the final customers for primary packaging for consumer chemicals. Data collection at this stage of the research was carried out using the group discussion method. The subsequent comparison of the results from both phases of the research enabled to identify suitable environmental innovations of primary plastic packaging, as well as barriers that will have to be overcome when implementing these innovations.
Keywords: sustainable packaging; consumer chemicals; plastic packaging waste